BMI and digitalisation: a contribution to the bibliometric debate. (29th October 2021) - Vito, Pietro; Iandolo, Francesca; Sala, Antonio La
The objective of this paper is to spark a debate on bibliometric methods of analysis and systematisation of scientific literature. The analysis is carried out about the impact of digitalisation on business models of firms, which are moreover currently conditioned by the pandemic emergency, but the discussion of the results and the conclusions are intuitively generalisable to any other theme. Specifically, a bibliometric analysis of our conception that does not belong to the methods of classical bibliometry is presented. The analysis is established on the coupling of scientific contributions by author keywords. The results obtained systematise the scientific literature according to a complementary perspective to those of the classical bibliometry and show how they lead to different but complementary conclusions, tracing the entire excursus of the analysis to the subjectivity of the scholar, contrary to what is generally shared in the literature on the objectivity of bibliometric methods.